Parâmetros vocais acústicos de sujeitos do sexo masculino antes, durante e após o processo de muda vocal - GUIMARÃES, Michelle Ferreira (Universidade Federal do Pará, 2013)
The voice and the vocal ability are different in every individual and in every stage of life. There is a limited number of studies on the vocal quality of children and adolescents during puberty. The aim of this study was to quantify the following parameters of acoustic analysis of voice: fundamental frequency, jitter, shimmer, harmonic-to-noise ratio and intensity. To understand the relationship between the voice and the development of children and adolescents, these parameters were correlated with each other and with the degree of pubertal development in male subjects. Methods: The subjects of the study were 110 males, aged between 11 and 20 years, students from three Macapá schools, where the data collection was carried out. The subjects were divided into 4 groups, 32 subjects aged between 11 and 12 years composed the Group I, 29 subjects aged between 13 and 15 the Group II, the Group III consisted of 30 subjects aged between 16 and 18 years and Group IV by subjects aged between 19 and 20 years. All subjects underwent computer-based voice recording using a unidirectional microphone. The following phonation tasks were requested: saying sustained vowel /é/, counting from 1 to 10 and reading a pre-established paragraph. Then, the subjects were assessed by a physician for characterization of pubertal development according to the stages described by Tanner. The voice analysis was performed using the voice acoustic program Vox Metria ®. Results: The subjects showed the following F0 average during sustained vowel: 223.28 Hz, 249.86 Hz, 122.63 Hz and 127.61 Hz for Groups I, II, III and IV respectively. The mean of F0 during the sequential speech was 217.09 Hz, 246.18 Hz, 117.27 Hz and 123.42 for Groups I, II, III and IV respectively. Shimmer showed increased values for the four groups. Jitter, intensity and harmonic noise ratio remained within normal limits established by the acoustic voice program used. Most subjects were in G3 (n = 38, 34.5%) and G4 (n = 42, 38.2%) and P3 (n = 34, 31%) and P4 (n = 36 , 32.7%) stages of pubertal development. The degree of pubertal development was correlated with F0 during speech (p <0.001) and with F0 during sustained vowel (p <0.001) and this correlation was statistically significant between G2 and G5, and G3 and G5. Conclusion: Subjects aging up to 15 years showed acoustic vocal parameters typical of the childish voice. The decrease of F0 occurs between 16 and 20 years old, but the voice is still in process of stabilization, with increased values of shimmer. F0 is the only parameter correlated with the degree of pubertal development. The last stage of voice change, in the studied population, is a late event in relation to pubertal development.